2017
DOI: 10.3390/polym9120673
|View full text |Cite
|
Sign up to set email alerts
|

Reorganizing Polymer Chains with Cyclodextrins

Abstract: During the past several years, we have been utilizing cyclodextrins (CDs) to nanostructure polymers into bulk samples whose chain organizations, properties, and behaviors are quite distinct from neat bulk samples obtained from their solutions and melts. We first form non-covalently bonded inclusion complexes (ICs) between CD hosts and guest polymers, where the guest chains are highly extended and separately occupy the narrow channels (~0.5-1.0 nm in diameter) formed by the columnar arrangement of CDs in the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
(128 reference statements)
1
5
0
Order By: Relevance
“…The endothermic peak shifted to a slightly higher temperature compared with that in the untreated films, which was from 125.8 to 127.2 °C. T g of the untreated PVAc/PMMA agrees well with the other reported results [ 57 , 58 ]. Similar results are obtained in the case of the other blend films (PVAc/PMMA 5:5), which demonstrate a higher thermal property (T g ) after the saponification treatment, which could be due to the conversion of PVAc/PMMA into PVA/P(MMA-MAA) blend films because PVA possesses a higher thermal property (Tg) than PVAc [ 59 ].…”
Section: Resultssupporting
confidence: 92%
“…The endothermic peak shifted to a slightly higher temperature compared with that in the untreated films, which was from 125.8 to 127.2 °C. T g of the untreated PVAc/PMMA agrees well with the other reported results [ 57 , 58 ]. Similar results are obtained in the case of the other blend films (PVAc/PMMA 5:5), which demonstrate a higher thermal property (T g ) after the saponification treatment, which could be due to the conversion of PVAc/PMMA into PVA/P(MMA-MAA) blend films because PVA possesses a higher thermal property (Tg) than PVAc [ 59 ].…”
Section: Resultssupporting
confidence: 92%
“…At the same time, the weight of the original HPβCD nanofibers continued to drop slowly after 383 °C. However, the weight of the HPβCD/DZ-IC nanofibers remained very stable after 386 °C, which indicated that an inclusion complex was formed between DZ and HPβCD and the thermal stability of DZ was improved. , …”
Section: Resultsmentioning
confidence: 98%
“…It appears that the amorphous regions are not sufficiently strong and connected to the crystalline regions by tie chains to permit sufficient structural rearrangement of the crystalline domains. Strategies exist to affect the crystallization morphology so that stronger connectivity could be established between spherulites and between lamellae, with the goal to improve mechanical properties of various semicrystalline polymers. Future work may adopt such approaches to determine whether the “self-nucleation” approach can improve ductility in well-crystallized PLLA.…”
Section: Tensile Extension Tests Below and Above T Gmentioning
confidence: 99%